Baudolino, une fascination sémiotique pour le mensonge - Mohamed Bernoussi (Cahiers de Narratologie)
Umberto Eco's fascination of lies is that of a semiotician for a human and semiotic phenomenon that lies at the crossroads of several issues relating to lies, narration and their close complicity that transcends our categories of thought as true and the false, the truth and the lie. Baudolino, the eponymous character of the novel, is a liar out of necessity to satisfy the thirst of men for stories that make people dream and trigger fears, hopes and obsessions. The purpose of this study is to examine the theme of lies in the novel, as well as the purely semiotic vision proposed by Umberto Eco.